Development Of Interactive Digital Modules On Flat Building Space Materials For Class IV Students - Dina Valentina F.T.H; Triman Juniarso; Via Yustitia (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2022)
Interactive digital modules for broad flat wake materials for grade IV students are motivated by, the variety of use of teaching materials, especially in mathematics learning in Kepuh Kiriman Elementary School 1. Interactive digital modules can be used to learn independently because students get feedback (scores) directly. The purpose of this research is to describe the process of developing interactive digital modules on broad flat wake materials for grade IV students and know their feasibility. This research uses a type of development research or commonly known as Research and Development (R&D). Using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). However, it is limited to the Analysis, Design and Development stage.Â  Data collection methods use questionnaires and documentation. Development research instruments used to assess the feasibility of interaktif digital modules are in the form of product feasibility questionnaires. Data analysis techniques use descriptive data analysis techniques for product processing and quantitative analysis to determine product feasibility. The results of this research are products of development results through three stages, namely Analysis (needs analysis, student analysis, content analysis / material), Design (the stage used to create an interactive digital module content framework) and Development (in the form of product development results.